The unsettled - Mathis, Ayana (New York : Alfred A. Knopf, 2023)
"Set in the 1980s in racially and politically turbulent Philadelphia and in the tiny town of Bonaparte, Alabama--about a mother fighting for her sanity and survival"--
From the moment Ava Carson and her ten-year-old son, Toussaint, arrive at the Glenn Avenue family shelter in Philadelphia 1985, Ava is already plotting a way out. She is repulsed by the shelter's squalid conditions: their cockroach-infested room, the barely edible food, and the shifty night security guard. She is determined to rescue her son from the perils and indignities of that place, and to save herself from the complicated past that led them there
Keywords: Mothers and sons -- Fiction; Nineteen eighties -- Fiction; Public shelters -- Fiction; Mothers and daughters -- Fiction; African Americans -- Fiction; African American families -- Fiction; Poor families -- Fiction; African American families -- Fiction; African American women -- Fiction; Mother-son relationship -- Fiction; Mother-daughter relationship -- Fiction; Abnormal psychology -- Fiction; Homelessness -- Fiction; Philadelphia (Pa.) -- Fiction; Philadelphia (Pa.) -- Fiction; Pennsylvania -- Fiction; Alabama -- Fiction; Domestic fiction; Historical fiction; Novels